SEGREGATION OF MICROPHYTOBENTHIC CHLOROPHYLL-A FROM SUSPENDED PARTICLES DURING TIDAL CYCLE IN NANAURA MUDFLAT, ARIAKE SEA, JAPAN - C.-H. Koh; J. S. Khim; H. Araki; H. Yamanishi; K. Koga (International Association of Lowland Technology, 2007)
The fluxes of microphytobenthic chlorophyll a (Chl-a) and suspended particulate matter (SPM) in water column and their relationship against tidal current have been examined during 15-days of full spring-neap tidal periods in the upper intertidal flat of Nanaura, Saga, Ariake Sea, Japan. The flood-ebb and spring-neap tidal conditions influenced within-day and daily variability in the fluxes of Chl-a and SPM, in terms of tidal energy. The Chl-a flux decreased relatively at slower pace than corresponding SPM flux at stage of decelerating incoming tide, which indicated the segregation of Chl-a from SPM followed by the slower settlement at depositional period. This ‘decoupling’ trend was consistently observed during the high tidal energy period of spring, particularly during the lower wind period (0-1 m s-1), but this was no more prevalent during the low tidal energy of neap and/or higher wind period (3-5 m s-1).